Influence of palm oil factory wastes as coarse aggregate species for green lightweight concrete - Huda, M.N.; Jumaat, Mohd Zamin; Islam, A.B.M.S.; Soeb, M.R. (Pontificia Universidad Catolica de Chile, Escuela de Construccion Civil, 2016)
Due to environmental issues, the use of waste materials in concrete is gaining popularity. Waste materials, such as oil palm shell (OPS) and palm oil clinker (POC) from the Malaysian palm oil industry are being used in various researches to produce lightweight concrete. Concrete containing only OPS shows more ductility and low compressive strength, while POC concrete shows less ductility but high compressive strength. The combination of OPS and POC may show improved compressive strength and ductility behavior. In this experimental study, the normal coarse aggregate is replaced by a mixture of OPS and POC aggregates in the lightweight concrete. The proportion of OPS and POC in the concrete mix varies from 40% to 70%. The results indicate that if a mixture of OPS and POC aggregate in producing lightweight concrete, better performance regarding compressive strength and ductility can be achieved. Furthermore, through the utilization of waste materials, the proposed lightweight concrete will help to mitigate the negative impact on the environment.